Etiologic Subtypes of Ischemic Stroke in SARS-CoV-2 Patients in a Cohort of New York City Hospitals - Tiwari, Ambooj; Berekashvili, Ketevan; Vulkanov, Volodomyr; Agarwal, Shashank; Khaneja, Amit; Turkel-Parella, David; Liff, Jeremy; Farkas, Jeffrey; Nandakumar, Thambirajah; Zhou, Ting; Frontera, Jennnifer; Kahn, David E.; et al. (Frontiers in Neurology, 2020)
Objective: To describe the ischemic stroke subtypes related to coronavirus disease 2019 (COVID-19) in a cohort of New York City hospitals and explore their etiopathogenesis. Background: Most neurological manifestations are non-focal, but few have reported the characteristics of ischemic strokes or investigated its pathophysiology. Methods: Data were collected prospectively April 1-April 15, 2020 from two centers in New York City to review possible ischemic stroke types seen in COVID-19-positive patients. Patient presentation, demographics, related vascular risk factors, associated laboratory markers, as well as imaging and outcomes were collected. Results: The age of patients ranged between 27 and 82 years. Approximately 81% of patients had known vascular risk factors, the commonest being hypertension (75%) followed by diabetes (50%) coronary disease or atrial fibrillation. Eight patients presented with large vessel occlusion (LVO) with median age 55 years (27-82) and all were male. Eight patients presented with non-LVO syndromes, with median age 65.5 years (59-82) and most were female (62.5%). Both groups were 50% African Americans and 37.5% South Asian. Both groups had similar D-dimer levels although other acute phase reactants/disease severity markers (Ferritin, CRP, procalcitonin) were higher in the LVO group. The LVO group also had a significantly higher mortality in the LVO group. The most common etiology was cryptogenic (6 patients) followed by small vessel occlusion (3 patients) & undetermined-unclassified (3 patients). For the remaining 4 patients, 2 were identified as cardioembolic and 2 with large artery atherosclerosis. Conclusion: COVID-19-related ischemic events can present as small vessel occlusions, branch emboli or large vessel occlusions. The most common etiology is cryptogenic. Patients with LVO syndromes tend to be younger, male and may have elevated acute inflammatory markers.